Pengaruh Pemberian Tepung Magot (Hermetia illucens) dalam Pakan Buatan Terhadap Pertumbuhan, Efisiensi Pakan Dan Kelangsungan Hidup Benih Ikan Mas (Cyprinus carpio L.) [The Feeding Effect Of Maggot Meal (Hermetia illucens) In Artificial Feed On Growth, Feed Efficiency And Survival Rate Of Common Carp Juvenile (Cyprinus carpio L.) ] - Yudi Cahyoko; Danita Garneda Rezi; Akhmad Taufiq Mukti (Jurnal Ilmiah Perikanan dan Kelautan, 2011)
Abstract Carp (C. carpio L.) is one commodity of fresh water fishery sector continues to grow rapidly in Indonesia. One of the factors that determine the success of aquaculture is the availability of sufficient feed, both in quantity and quality. The aim of this research was to find out optimum percentage of feeding maggot meal in artificial feed on growth, efficiency of feed and survival rate of common carp juvenile. The treatment of this researh was feeding maggot meal in artificial feed i.e. 0%, 5%, 10%, 15%, and 20%. The design of this research was Completely Randomized Design. Data analysis used Analysis of Variance (ANOVA) to know the effect of the treatment and the difference among the treatment used Duncan's Multiple Range Test (DMRT). The result of this research showed that the growth, efficiency of feed and survival rate of common carp that given maggot meal in artificial feed was not significantly (P>0,05). Water quality on culture medium, temperature, pH, dissolved oxygen, and ammonia was 2832oC, 7-8, 5 mg/L and 0,02-0,05mg/L respectively.